University libraries: use of strategies communications to combat disinformation in the context pandemic Covid-19 - Vidarte, Vanessa Cristiane Dornelles; Velasco, Shana Catiusca Dornelles Vidarte (Biblioteca Escolar em Revista, 2021)
The advent of the "informational society" (CASTELLS, 1999) emerges dedicating space to information. Although so relevant to this society, the extensive volume of information disseminated through social media favors the dissemination of false information. Recently, the World Health Organization declared that the Covid-19* pandemic has generated an infodemic, a phenomenon that further aggravates the current public health crisis. In light of the above, this article aims to analyze how university libraries can contribute to controlling disinformation, through the use of communication strategies. For this purpose, as a methodological procedure a literature review was conducted relating the topics: informational society and its challenges as "post-truth" (DELFINO et al., 2019) and infodemic, misinformation and formation of public opinion, as well as a mapping in the websites and social media of some university libraries, in the period of paralysis of in-person activities. As a result, we verified that post-truth has become a consequence of society, said to be ‘informational’, but which does not know how to use information properly. Moreover, it was understood that misinformation is a strategy for manipulating public opinion since it interferes with the individuals' ability to interpret and evaluate information. It was found that the libraries studied have effectively used communication strategies such as the dissemination of informational content on social media, which assist users in the critical evaluation of the information received. It is concluded that university libraries, as mediators of the user's interaction and relationship processes with information, play an important role in combating disinformation.